Docking, Molecular Dynamics Simulation and Synthesis of New Fenobam Analogues as mGlu5 Receptor Antagonists - Javidan, Abdollah; Javad Taghizadeh, Mohammad; Ayoub Hosseini, Seyed; Iman, Maryam; Jafari, Rahim (Combinatorial Chemistry & High Throughput Screening, 2016)
Background: Fenobam is a non-competitive mGluR5 antagonist as an anxiolytic agent. Objective: In this research a new series of fenobam analogues containing thiazole moiety instead of imidazole ring were designed and synthesized. Methods: The ureido-substituted products were synthesized from reaction of amino thiazole derivatives and isocyanate derivatives in dichloromethane solvent under microwave and ultrasonic irradiation condition. The synthesized compounds structures were established by means of IR, 1HNMR, 13CNMR spectroscopic data. Then, docking calculations were performed on the active site of mGLuR5 and compared to Fenobam as a reference drug by using AutoDock program. The molecular dynamics (MD) simulations were done using GROMACS 5.0.5. Results: Docking studies suggested that all of the compounds possess better binding energy when compared to fenobam. The results of MD simulations might offer the binding mode of ligand (3b), accuracy of docking and the reliability of active conformations which obtained by AutoDock. Conclusion: New derivatives of fenobam were designed and synthesized that have the better insilico results compared to fenobam and will evaluate in future studies.
Keywords: Isocyanates